The causal effects of the minimum wage introduction in Germany: An overview - Marco Caliendo; Carsten Schröder; Linda Wittbrodt (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
In 2015, Germany introduced a statutory hourly minimum wage that was not only universally binding but also set at a relatively high level. We discuss the short-run effects of this new minimum wage on a wide set of socio-economic outcomes, such as employment and working hours, earnings and wage inequality, dependent and selff-employment, as well as reservation wages and satisfaction. We also discuss diffculties in the implementation of the minimum wage and the measurement of its effects related to non-compliance and suitability of data sources. Two years after the minimum wage introduction, the following conclusions can be drawn: while hourly wages increased for low-wage earners, some small negative employment effects are also identifiable. The effects on aspired goals, such as poverty and inequality reduction, have not materialized in the short run. Instead, a tendency to reduce working hours is found, which alleviates the desired positive impact on monthly income. Additionally, the level of non-compliance was substantial in the short run, thus drawing attention to problems when implementing such a wide reaching policy.
Keywords: J22; J23; J31; J38; 330; Minimum wage; Evaluation; Earnings; Working hours; Employment